17-4 PH SS Manufactured via Selective Laser Melting: High Cycle Fatigue Properties. Issue 1 (October 2021) - Fraccaroli, Lorenzo; Concli, Franco
Abstract: In the recent years, Additive Manufacturing (AM) is becoming an emerging technology and more and more material powders are available on the market. The knowledge of their specific mechanical behaviour is a fundamental aspect for their large-scale adoption, also considering the lack of reliable data and dedicated standards.In this work the High Cycle Fatigue characterization of a 17-4 PH Stainless Steel (SS) is presented. The cylindrical samples used were manufactured via Selective Laser Melting (SLM) technology using an EOS M280 machine. Two separate series of samples differing in terms of surface finishing were tested. The first series of samples was used in the as-build condition while the second series was machined in order to obtain a better surface finishing.The effect of the surface finishing on the fatigue behaviour of AM materials is fundamental considering that in most of the applications the parts – reticular or lattice structures with complex geometries – are set into operation in the as-build condition because a surface finishing is not feasible. The comparison of the results obtained for the two different series of specimens allows the quantification of the reduction of the mechanical performances due to the actual limits of the SLM technology. The fatigue limit was obtained with the short stair-case approach according to the Dixon statistical method. The maximum number of cycles (run-out) was set equal to 5000000. The left part of the Wöhler diagram was also studied by means of additional tests at higher stress levels.Additional quasi-static tests were performed in order to characterise the static behaviour.